Utilizing Google Classroom to Promote Students’ English Language Skills: A systematic Review - Suci Ramadhani; Sulistiyani Sulistiyani; Khoiriyah Khoiriyah (STKIP PGRI Tulungagung, 2023)
This research is based on the analysis results of observations and experiences of the researcher, in which in 21st century learning both teachers and students must have good technology skills. This can be implemented through learning using a platform that can support students in improving their English skills. The aims of this research are to answer (1) How is the implementation of Google Classroom to teach English? (2) How could Google Classroom promote students' English language skills? This study uses a qualitative approach with a systematic review method. Ten out of twenty research articles were selected using an internet search based on inclusion-exclusion criteria. To analyze the data, this research used thematic analysis as a technique of analyzing data. The result showed that (1) Google Classroom helped students with various features that can facilitate students in the English learning process. (2) The success of Google Classroom can be seen from the improvement of students' English skills. Further, Google Classroom was useful, easy to use, and enjoyable tool for students to improve their English skills. Thus, Google Classroom platform significantly helps improve the students’ quality of English learning.